The Nexus between Agriculture and Renewable Energy Sources in the Island of Crete, Greece. - Vourdoubas, John (European Journal of Applied Sciences, 2020)
The aim of the current work is the study of the nexus between agriculture and renewable energies in the island of Crete, Greece. Agriculture and the use of renewable energies for energy generation are important sectors of the Cretan economy. Various applications of renewable energy systems in rural areas of Crete are presented. Use of agricultural residues and by-products for fuel production and energy generation are also described. Solar energy, wind energy, biomass and small hydroelectric systems are used for electricity and heat generation in rural areas in the island. Various residues and by-products produced mainly by olive trees are used for heat generation. The links of agriculture and renewable energies in the island should be strengthened in the future. Use of renewable energies in Crete has positive impacts in climate change mitigation while the impacts of agriculture are both positive and negative. Both sectors have positive impacts in the development of rural areas in the island. Agriculture and renewable energy use constitute complementary sectors to the tourism industry which dominates the island’s economy and they should be promoted in the future in order to achieve a multi-dimensional and equally balanced economic development in Crete.